Odpowiedź :
a) 7x - 1
[tex]dla \ x = -4\\7x -1 = 7\cdot(-4)-1 = -28-1 = -29\\\\dla \ x = 5\\7x-1 = 7\cdot5-1 = 35 - 1 = 34\\\\dla \ x = 0\\7x - 1 = 7\cdot0 - 1 = 0-1 = -1[/tex]
b) 6 - x
[tex]dla \ x = 3\\6-x = 6-3 = 3\\\\da \ x = -2\\6-x = 6-(-2) = 6+2 = 8\\\\dla \ x = 0\\6-x = 6-0 = 6[/tex]
c) x(9 - x)
[tex]dla \ x = 5\\x(9-x) = 5(9-5) = 5\cdot4 = 20\\\\dla \ x = 8\\x(9-x) = 8(9-8) = 8\cdot1 = 8\\\\dla \ x = -3\\x(9-x) = -3(9 - (-3)) = -3(9+3) = -3\cdot12 = -36[/tex]
d) 8 - 4x
[tex]dla \ x = 3\\8-4x = 8-4\cdot3 = 8 - 12 = -4\\\\dla \ x = -3\\8-4x = 8 - 4(-3) = 8 + 12 = 20\\\\dla \ x = \frac{1}{4}\\8-4x = 8 - 4\cdot\frac{1}{4} =8-1 = 7[/tex]